Design Aid for Required Moment of Inertia of Simple Beams - Eisenman, Mark L. (Engineering Journal, 1989)
The AISC Manual of Steel Construction and other publications include tables which permit calculation of beam deflections for simple loading cases after a preliminary section has been selected. To design for a specific deflection criterion, these tables may be used in iterative fashion for a series of trial sections, or the formulas may be inverted to solve for a required moment of inertia when the limiting deflection is known. In either case, use of the formulas is cumbersome and prone to error, especially in converting to consistent units. Presented here is a table of formulas which permit direct solution for required moment of inertia for several simple loading cases, for the two most common deflection criteria, L/240 and L/360. The author has found these formulas much simpler and quicker to use, because the constants in the formulas already incorporate the conversion factors for commonly used units.